SISTEM PERINGATAN DINI BANJIR DUAL PLATFORM - Basuki, Arif; Septi Savitri; Tugino (Institut Teknologi Nasional Yogyakarta, 2022)
Indonesia has a tropical climate with high rainfall intensity. This often leads to catastrophic flooding during heavy rains. This study aims to monitor the height and flow of river water online which is the initial information about the coming flood disaster. In supervision, using the ESP32 microcontroller technology approach based on the Internet of Things (IoT) is intended to obtain real time information on height and water discharge. In this system the ultrasonic sensor HC-SR 04 is used as a water level reader, the flowrate sensor is used as a water flow reader, the 20x4 LCD is used as a display of the sensor reading results, the LED is used as an indicator light and the speaker is used as a sound notification, and sends data wirelessly. to the Blynk, ThingsSpeak and Telegram apps. In this system, the detection of water level uses an ultrasonic sensor with 3 parameter values ​​that have been made, namely, water height is more than 30 cm, the status read is dangerous, water height is more than 20 cm and less than 30 cm, the status read is standby 2 and water level is less than 20 cm then the status read is safe. Detection of water discharge level using a flowrate sensor with a water discharge parameter value of more than 9 L / min then the status read is standby 1.